2018
DOI: 10.2147/dmso.s181154
|View full text |Cite
|
Sign up to set email alerts
|

Madelung’s disease – progressive, excessive, and symmetrical deposition of adipose tissue in the subcutaneous layer: case report and literature review

Abstract: Madelung’s disease is a rare disorder described for the first time in the year 1846 by Brodie. It is characterized by the occurrence of progressive, excessive, and symmetrical deposits of adipose tissue in the subcutaneous layer. Most often, these changes concern the neck, the nape of the neck, arms, and upper back, giving the patients a specific, pseudoathletic appearance. Madelung’s disease is also known as multiple symmetrical lipomatosis, benign symmetrical lipomatosis, and Launois-Bensaude syndrome. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 22 publications
1
30
0
2
Order By: Relevance
“…Patients with MSL present features of symmetrical fat localization on their neck, shoulder, trunk, upper arms, and occiput [ 1 , 3 , 13 15 ]. MSL is often confused with simple obesity by its similar clinical features and symptoms, hence it is important to identify key hallmarks to differentiate the two conditions [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MSL present features of symmetrical fat localization on their neck, shoulder, trunk, upper arms, and occiput [ 1 , 3 , 13 15 ]. MSL is often confused with simple obesity by its similar clinical features and symptoms, hence it is important to identify key hallmarks to differentiate the two conditions [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to unknown reasons, cases of the disease have been more frequently reported in specific geographical areas (e.g., the Mediterranean region) [ 4 , 7 ]. However, the condition has only rarely been reported in Asian females [ 8 , 9 ]. In this report, we present a case of an Asian female with MSL.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The cause of the disease remains unknown, but alcohol abuse is an important risk factor in MSL development and avoidance of alcohol consumption may prevent disease progression. [9][10][11] Furthermore, other factors, like diabetes, hyperlipidemia, fatty liver, obstructive sleep apnea syndrome (OSAHS), or other metabolic diseases, were also reported to be associated with MSL development, 12 although Harsch IA and we showed normal metabolic parameters in MSL patients. 13,14 Molecularly, gene mutation or deletion was associated with MSL development.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, MD diagnosis is reached through anamnesis, clinical examination, X-ray computed tomography, or magnetic resonance imaging. Moreover, though other studies report a lack in comorbidities, the disease has been frequently associated with alcoholism, liver disorders, diabetes, and dyslipidemia [5]. The only available treatment for this disease is surgery, through fat tissue excision, liposuction, or a combination of both but is sadly not definitive due to its high recurrence rate.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, new therapeutic strategies targeting pathogenetic mechanisms are requested. Indeed, several studies tried to elucidate the biology underneath the pathology without reaching a definitive conclusion [5,6]. In fact, it has been reported that MD tissues and cells show aberrant growth, mitochondrial energy metabolism, brown fat tissue alterations, and adipogenic index, ascribing these phenomena to specific proteins, such as Uncoupling Protein (UCP)-1 (a brown adipocyte marker) [7,8], calcyphosine-like (CAPSL) protein [9], or microRNAs such as miR-125a-3p and miR-483-5p, all associated with adipogenesis or fatty acid oxidation in peroxisomes [10].…”
Section: Introductionmentioning
confidence: 99%